2023
DOI: 10.21203/rs.3.rs-2947906/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Analysis of thermal discomfort associated with synoptic conditions in the city of Pelotas, extreme south of Brazil

Abstract: This study aims to evaluate the outdoor environment conditions (synoptic weather conditions) on extreme events of human thermal discomfort in the city of Pelotas, Brazil, between 18th January and 20th August, 2019. Digital thermohygrographs were installed outside the residences in order to record of air temperature data, dew point temperature and air relative humidity. Five different macro-regions of the city were analyzes applying two different biometeorological indices. For the summer months, the Humidex Ind… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
(9 reference statements)
0
0
0
Order By: Relevance
“…During the early morning hours (6:00 am-9:00 am), DIK values are relatively low, indicating thermal comfort or mild heat discomfort. This behavior can be attributed to the lower ambient temperatures and higher relative humidity typical of this period, as observed by Trassante et al (2024), who reported discomfort due to lower temperatures in the early morning hours in similar studies.…”
Section: Resultssupporting
confidence: 65%
“…During the early morning hours (6:00 am-9:00 am), DIK values are relatively low, indicating thermal comfort or mild heat discomfort. This behavior can be attributed to the lower ambient temperatures and higher relative humidity typical of this period, as observed by Trassante et al (2024), who reported discomfort due to lower temperatures in the early morning hours in similar studies.…”
Section: Resultssupporting
confidence: 65%